Paritas dan Body Condition Score (BCS) Ternak Sapi Bali di Wilayah Kanusuang, Sulawesi Barat - Ummul Masir; Santi; Andi Fausiah (Universitas Sulawesi Barat, 2020)
The study aims to provide an overview of the value of the body condition and parity of Bali cattle in the Kanusuang region, West Sulawesi. A total of 11 Bali cows that have been given birth once were involved in this study. Data were collected by direct observation of Bali cows in the field and interview toward the farmers. All cows were subjected to body condition scoring (BCS; scale 1 - 5) through visual measurement. The results of this study showed that most of the proportion of Bali cattle with parity 1 and 2 were the same, 36,36%, while parity 3 was 27,2%. There were 15,4% of the total sample observed cattle have BCS value 3, followed by BCS values 4 and 5 respectively 46,1% and 38,5%. The correlation test between parity and BCS obtained value r=0,355 (P>0,05) means no correlation between both of the data. The BCS value of livestock belonging to farmers in the study location was in the normal range, which refers to the standard BCS values 1-5. The parity value obtained cannot be used as a standard for determining reproductive performance, but was invented as an evaluation of reproductive efficiency.